ASSA13-02-15 Clinical Characteristics of 4 Cases of Polymorphic Ventricular Tachycardia/Ventricular Fibrillation Initiated by Idiopathic Premature Ventricualr Contraction Originating from Right Ventricular Outﬂow Tract. (29th April 2013) - Yan-chun, Liang; Zu-lu, Wang; Ming, Liang; Shi-bei, Li; Zhi-qing, Jin; Ya-ling, Han
Abstract : Background: Ventricular ﬁbrillation and/or polymorphic ventricular tachycardia are occasionally initiated by ventricular extrasystoles originating from the right ventricular outﬂow tract (RVOT) in patients without structural heart disease. Objective: The aim of this study was to report clinical characteristics of 4 cases of polymorphic ventricular tachycardia/ventricular fibrillation (PVT/VF) initiated by idiopathic premature ventricualr contraction (PVC) originating from RVOT. Methods: Among 76 patients with ventricular tachycadia (VT) arising from RVOT, the clinical characteristics of 4 patients with PVT/VF triggered by PVC originating from RVOT were investigated and compared with the clinical characteristics of the other 72 patients. Results: The same PVC morphology was shown in triggering PVCs that initiated PVT/VF and in isolated PVCs. The coupling intervals of the above two kinds of PVCs were markdly different. The coupling intervals of triggering PVCs were shortened in 2 cases and prolonged in the remain 2 cases compared with those of isolated PVCs, and the variation magnitude of the coupling interval in every case was more than 70 ms. The coupling intervals of isolated PVCs were not fixed in 1 case. The number of PVCs per day, the coupling interval of isolated PVC and the baseline QT interval were 15427 ± 1109, 419 ± 22ms and 404 ± 15ms respectively in 72 monomorphic VT patients. The numbers of PVCs per day of 3 of the 4 PVT/VF patients were equivalent to those of 72 VT patients, and the same equivalence was found in the coupling intervals of isolated PVC and the baseline QT intervals of the 4 patients. The cycle lengths of PVT/VF were all less than 280 ms, which was shorter than that of monomorphic VT (324 ± 59ms) obviously. Among 4 patients, episodes of syncope were documented in 2 patients, and the syncope rate of 72 VT patients was 4.1%. Activating mapping and pacing mapping confirmed that the PVCs of all these 4 patients originated from septal of RVOT, and PVCs were successfully eliminated by radiofrequency catheter ablation. Conclusions: PVCs that triggered PVT/VF and originated from tract RVOT had the characteristics of unstable coupling intervals and short circle lenth of PVT/VF. Radiofrequency catheter ablation was effective as a treatment option for these patients.